The impact of digital marketing on gen Z's Mangrove eco-tourism brand loyalty in Vietnam - Nhung, Nguyen Thi; Phuong, Nguyen Linh (Edelweiss Applied Science and Technology, 2025)
The article examines the relationship between digital marketing tools and customers' mangrove eco-tourism brand loyalty using a linear regression model with a sample size of 750 customers distributed in three major cities in Vietnam, namely Hanoi, Da Nang, and Ho Chi Minh City. Research indicates that digital marketing tools, including websites, display advertising, search engine optimization, and social media, influence customers' mangrove eco-tourism brand loyalty. Moreover, research results suggest two new factors: display advertising and social media help enhance brand awareness among Gen Z, and word-of-mouth marketing effectiveness from current customers to potential customers significantly affects Gen Z's mangrove eco-tourism brand loyalty.